Fast setting silk fibroin bioink for bioprinting of patient-specific memory-shape implants - Costa, João B. (2017)
The pursuit for the â perfectâ biomimetic and personalized implant for musculoskeletal tissue regeneration remains a big challenge. 3D printing technology that makes use of a novel and promising biomaterials can be part of the solution. In this study, a fast setting enzymatic-crosslinked silk fibroin (SF) bioink for 3D bioprinting is developed. Their properties are fine-tuned and different structures with good resolution, reproducibility, and reliability can be fabricated. Many potential applications exist for the SF bioinks including 3D bioprinted scaffolds and patient-specific implants exhibiting unique characteristics such as good mechanical properties, memory-shape feature, suitable degradation, and tunable pore architecture and morphology.